2017
DOI: 10.1080/10428194.2017.1283031
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability is a principle pathologic feature of FLT3 ITD kinase activity in acute myeloid leukemia leading to clonal evolution and disease progression

Abstract: Acute Myeloid Leukemia with FLT3 ITD mutations are associated with a poor prognosis characterized by a higher relapse rate, shorter relapse free survival, and decreased likelihood of response to therapy at relapse. FLT3 ITD signaling drives cell proliferation and survival. FLT3 ITD AML disease progression is associated with cytogenetic evolution and acquired tyrosine kinase inhibitor (TKI) resistance suggesting a potential role of genomic instability. There is growing evidence demonstrating a relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 93 publications
(118 reference statements)
1
22
0
Order By: Relevance
“…Several studies have recently demonstrated a pervasive dysregulation of genomic stability in several cancers, including AML. 8 , 38 To explore whether observed high SIRT6 expression was related to the constitutive DNA damage and intense replicative stress observed in AML cells, we used a chromosomal instability signature (CIN)16 to categorize AML cell lines included in a published dataset (GSE59808). A subset of approximately 40% AML cell lines demonstrated overexpression of probe sets belonging to CIN-signature ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have recently demonstrated a pervasive dysregulation of genomic stability in several cancers, including AML. 8 , 38 To explore whether observed high SIRT6 expression was related to the constitutive DNA damage and intense replicative stress observed in AML cells, we used a chromosomal instability signature (CIN)16 to categorize AML cell lines included in a published dataset (GSE59808). A subset of approximately 40% AML cell lines demonstrated overexpression of probe sets belonging to CIN-signature ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…ITDs constitute a rare category of gene mutations in which a segment of a coding region of a gene is duplicated in an end‐to‐end manner. Although the exact mechanism remains unclear, several studies have suggested genomic instability accompanied by erroneous DNA repair mechanisms to be key elements contributing to this phenomenon . Very recently, an epidermal growth factor receptor ( EGFR ) ITD was reported in a DN CCSK originating from a horseshoe kidney.…”
Section: Discussionmentioning
confidence: 99%
“…These effectors interact with the PI3K/Akt/mTOR pathway, elucidation of which may reveal possible mechanisms of resistance to PI3K-directed therapies. Recent studies have stressed that FLT3-ITD induces genomic instability through ROS production, which potentially contributes to chemoresistance leading to disease relapse [132,133]. The PI3K/Akt/mTOR signaling pathway is linked to both ROS production and the DNA damage response (DDR) pathway, strengthening the premise of further exploiting this pathway as a potential therapeutic target [46,134,135].…”
Section: Crosstalk Of the Pi3k/akt/mtor Signaling Pathway With Other mentioning
confidence: 99%
“…In a previous section, we briefly highlighted the importance of increased ROS in AML, which can promote genomic instability and contributes to chemotherapy resistance. In particular, there is increasing evidence associating FLT3 mutations with DNA damage, specifically through increased ROS, resulting in double strand breaks (DSBs) and impaired DNA repair [132,306]. Targeting DNA damage repair mechanisms may provide a novel therapeutic opportunity in AML that may reduce repair errors and genomic instability [307].…”
Section: Pi3k/akt/mtor Inhibitors In Combination With Dna Repair Inhimentioning
confidence: 99%